Spectrophotometric Method for the Determination of Atmospheric Cr Pollution as a Factor to Accelerated Corrosion - Dereje Homa; Ermias Haile; Alemayehu P. Washe (Journal of Analytical Methods in Chemistry)
The effect of Cr(VI) pollution on the corrosion rate of corrugated iron roof samples collected from tanning industry areas was investigated through simulated laboratory exposure and spectrophotometric detection of Cr(III) deposit as a product of the reaction. The total level of Cr detected in the samples ranged from 113.892 ± 0.17 ppm to 53.05 ± 0.243 ppm and showed increasing trend as sampling sites get closer to the tannery and in the direction of tannery effluent stream. The laboratory exposure of a newly manufactured material to a simulated condition showed a relatively faster corrosion rate in the presence of Cr(VI) with concomitant deposition of Cr(III) under pH control. A significant (P = 0.05) increase in the corrosion rate was also recorded when exposing scratched or stress cracked samples. A coupled redox process where Cr(VI) is reduced to a stable, immobile, and insoluble Cr(III) accompanying corrosion of the iron is proposed as a possible mechanism leading to the elevated deposition of the latter on the materials. In conclusion, the increased deposits of Cr detected in the corrugated iron roof samples collected from tanning industry zones suggested possible atmospheric Cr pollution as a factor to the accelerated corrosion of the materials.